2013
DOI: 10.1177/030089161309900622
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Adverse Events Complicating the Administration of Rituximab: Report of Two Cases

Abstract: Rituximab is a murine/human chimeric monoclonal antibody directed against the CD20 antigen. It is widely used in combination with polychemotherapy regimens for the treatment of hematological disorders. There is no evidence of direct cardiotoxicity of the drug but a few cases of cardiovascular adverse events have been reported in the literature. We report on two patients affected by stage IV non-Hodgkin lymphoma with bone marrow infiltration and peripheral blood involvement who experienced cardiovascular accide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…67 Two patients presented several cardiovascular risk factors the administration of rituximab. 68 This journal is © The Royal Society of Chemistry 2016 association links generated from the comprehensive human interactome provides a unique and rich network data set for exploratory analysis and hypothesis testing regarding drug action and benefit. The summary provided here only begins that exploratory process, which can evolve much more comprehensively in future studies.…”
Section: Pharmacological Insights Derived From Network Analysismentioning
confidence: 99%
“…67 Two patients presented several cardiovascular risk factors the administration of rituximab. 68 This journal is © The Royal Society of Chemistry 2016 association links generated from the comprehensive human interactome provides a unique and rich network data set for exploratory analysis and hypothesis testing regarding drug action and benefit. The summary provided here only begins that exploratory process, which can evolve much more comprehensively in future studies.…”
Section: Pharmacological Insights Derived From Network Analysismentioning
confidence: 99%
“…Cisplatin, when administered intravenously, intrapericardial, or intrathoracically, can cause acute AF in 10%–32% of patients ( Tomkowski and Filipecki, 1997 ; Tomkowski et al, 2004 ; Bischiniotis et al, 2005 ; Lara et al, 2005 ; Richards et al, 2006 ; Tilleman et al, 2009 ; Zellos et al, 2009 ). A systematic review showed that standard doses of gemcitabine, immune checkpoint inhibitors, Marfan, abiraterone acetate, and rituximab can increase the incidence of atrial fibrillation in elderly patients, those with reduced renal function, or those with hypertension ( Olivieri et al, 1998 ; Phillips et al, 2004 ; Mileshkin et al, 2005 ; Feliz et al, 2011 ; Passalia et al, 2013 ; Sharma et al, 2017 ; Hilmi et al, 2020 ; Mascolo et al, 2023 ). In addition, high doses of cyclophosphamide and isocyclophosphamide increase the risk of paroxysmal AF ( Kupari et al, 1990 ; Quezado et al, 1993 ).…”
Section: Types Of Arrhythmias Caused By Chemotherapy Drugsmentioning
confidence: 99%
“…Препарат широко применяется для лечения онкогематологических заболеваний. Описаны его побочные эффекты со стороны сердечно-сосудистой системы, включая ФП, возникающую во время или сразу после инфузии ритуксимаба в стандартных дозах (375 мг/м 2 ) [53]. Во II фазе многоцентрового исследования 120 пациентам с B-клеточными лимфомами ритуксимаб вводился в течение 4 нед [54].…”
Section: таргетная терапия ритуксимабunclassified